District/City Grouping Based On Factors Affecting The Level Poverty In North Sumatera With Using Cluster Analysis - Fadhillah, Nurul; Rakhmawati, Fibri; Widyasar, Rina; Husein, Ismail (ZERO: Jurnal Sains, Matematika dan Terapan, 2019)
Poverty is a person's inability to fulfill the aspects of life. To overcome the problem of poverty, there are some factors which affect the poverty levels that need to be considered. The factors that influence the poverty levels are economic growth, unemployment, and education. Poverty in each region has different characteristics, and therefore it is necessary to group the regions so that the solutions can be implemented in accordance with each of the characteristics of the region. The purpose of this study is to cluster districts/cities in North Sumatra in accordance with the factors that affect poverty levels in each region using cluster analysis based on the centroid linkage method. Cluster analysis is a grouping into clusters so that objects in a cluster are more similar to each other than the objects in other clusters. From the clustering result of cluster analysis by using the centroid linkage method shows that there are four groups of districts/cities which are incorporated based on each factor that affects poverty levels, namely, economic growth, unemployment, and education.